(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Vera F, Wajjwalku W, Yuda P, Daryono BS. 2021. Short Communication: A new primer set in CHD1 gene for bird sex identification. Biodiversitas 22: 4977-4982. Determine sex is difficult for many bird species that are sexually monomorphic or only dimorphic in the adult stage. Many molecular markers have been developed for DNA sexing, which were mostly based on identifying Z and W chromosomes of avians. The sex determination of birds was mostly applied universal primer set such as P2/P8 or 2550F/2718R. However, those universal primers that were designed sometimes could not good result consistency in non-ratite birds or ratite birds. Therefore, we improved a specific primer design with deletion site in W chromosome to amplify the female-specific segments on Chromodomain-helicase DNA binding protein-1 (CHD1) gene from alignment sequences CHD1-Z and CHD1-W of Macrocephalon maleo S. Müller, 1846. This study aims to design a new pair of primer targeting a section of the CHD1 gene that can be amplified in non-ratite birds, the name of a new primer is In-Sex F/In-Sex R. A new primer set amplified DNA fragments in around 650 or 550 base pairs of CHD1-Z and also, 350 base pairs of CHD1-W. The result has successfully amplified the sex of multiple species on orders Galliformes, Passeriformes, Accipitriformes, and Strigiformes. This analysis can be helpful to the effort of in-situ or ex-situ management and conservation programs e.g the mating system in birds. And also, the analysis can be helpful for sexing data in the case of captive birds before releasing in natural habitat or reintroduction programs.